Gene expression profiles in guided bone regeneration using combinations of different biomaterials: a pilot animal study. Issue 6 (29th May 2016) - Suleimenova, Dina; Hashimi, Saeed M.; Li, Ma; Ivanovski, Saso; Mattheos, Nikos
Abstract: Objectives: The aim of this study was to investigate the gene expression profile related to guided bone regeneration (GBR) at the early healing stage while using combinations of different biomaterials. Materials and methods: Cranial defects in 4 New Zealand rabbits were filled with A) biphasic calcium phosphate/experimental pericardium‐derived collagen membrane, B) Bio‐Oss ® /Bio‐Gide ®, C) biphasic calcium phosphate/strontium hydroxyapatite‐containing collagen membrane and D) Bio‐Oss ® /strontium hydroxyapatite‐containing collagen membrane. Seven days after surgery, one animal was subjected to histological observation and histomorphometric analysis, and three animals to real‐time quantitative reverse transcription polymerase chain reaction (PCR). An RT 2 Profiler PCR Array (PANZ‐026Z, QIAGEN, QIAGEN Sciences, Germantown, MD, USA) was conducted to observe the gene expression profile of groups A, C and D as compared with the control group B. Results: The analysis showed 9 of the 84 genes on the array to be significantly different in the three experimental groups (six genes in group D, four in group C and one in group A). Group D demonstrated the most changes in gene expression profile at day 7. Genes that were significantly down‐regulated (AHSG, EGF) or up‐regulated (CDH11, MMP13, GLI1 and MCSF) are responsible for early‐stage bone formation, bone remodeling and pre‐osteoclast development. The gene expression profile of this group correlated with the histological findings, as this group showed the higher formation of osteoid as compared with the other groups. Conclusion: Gene expression patterns at early‐stage healing of GBR‐treated defects appear to be related to the biomaterial used. The combination of Bio‐Oss ® and strontium hydroxyapatite‐containing collagen membrane showed the most pro‐osteogenic gene regulation profile (group D), implying the stimulation of key transcriptional factors, which appeared to translate into the up‐regulation of the osteogenic process and earlier bone formation.